2001
DOI: 10.1074/jbc.m103166200
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3β Regulates GATA4 in Cardiac Myocytes

Abstract: Inactivation of glycogen synthase kinase 3␤ (GSK3␤)is critical for transcription of atrial natriuretic factor (ANF) by ␤-adrenergic receptors in cardiac myocytes. We examined the mechanism by which GSK3␤ regulates ANF transcription. Stimulation of ␤-adrenergic receptors induced nuclear accumulation of GATA4, whereas ␤-adrenergic ANF transcription was suppressed by dominant negative GATA4, suggesting that GATA4 plays an important role in ␤-adrenergic ANF transcription. Interestingly, GATA4-mediated transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(161 citation statements)
references
References 65 publications
7
148
1
5
Order By: Relevance
“…The role of GSK-3β as a potential drug target has become more and more prominent in the last years (Phukan et al 2010). Several studies reported that inhibition of GSK-3β by selective small molecules is protective in clinically relevant disease models: GSK-3β inhibition was shown to improve insulin resistance in type II diabetes (Gum et al 2003;Ring et al 2003), to have beneficial effects in neurological disorders like Alzheimer's disease (Hsiung et al 2003) and to reduce cardiac hypertrophy and ischaemia (Morisco et al 2001). Despite increasing evidence for the therapeutic potential of GSK-3β inhibition to counteract various cytotoxic stressors, to our knowledge, there are no studies investigating GSK-3β inhibition in the model of experimental PD.…”
Section: Discussionmentioning
confidence: 99%
“…The role of GSK-3β as a potential drug target has become more and more prominent in the last years (Phukan et al 2010). Several studies reported that inhibition of GSK-3β by selective small molecules is protective in clinically relevant disease models: GSK-3β inhibition was shown to improve insulin resistance in type II diabetes (Gum et al 2003;Ring et al 2003), to have beneficial effects in neurological disorders like Alzheimer's disease (Hsiung et al 2003) and to reduce cardiac hypertrophy and ischaemia (Morisco et al 2001). Despite increasing evidence for the therapeutic potential of GSK-3β inhibition to counteract various cytotoxic stressors, to our knowledge, there are no studies investigating GSK-3β inhibition in the model of experimental PD.…”
Section: Discussionmentioning
confidence: 99%
“…We too have demonstrated that DOX interferes with GATA-4 DNA binding but also that CO restores cardiac GATA-4 activity, alone as well as after DOX, thereby connecting it directly to the GATA-4 antiatrophic effect. Akt1 positively regulates GATA-4 transactivation in cardiomyocytes via phosphorylation and inactivation of GSK3β (28), and here DOX reduces pGSK3β, a negative regulator of GATA-4 in the nucleus. CO increases GSK3β phosphorylation and thereby functionally inactivates GSK3β.…”
Section: Discussionmentioning
confidence: 99%
“…This result strongly implicates Akt1, via Bad phosphorylation, in the protection against DOXinduced apoptosis by CO. And because Akt1 negatively regulates GSK3β activation, and GSK3β negatively regulates nuclear GATA-4 (26), GSK3β is implicated in the low GATA binding levels. CO increases phospho-GSK3β levels, decreasing GSK3β activation, a known factor in GATA-4 transcriptional activation (28).…”
Section: Figurementioning
confidence: 99%
“…GATA-4 actions involve combinatorial interactions with other cell-restricted or inducible transcription factors, including Nkx2.5, Mef2, SRF, nuclear factor of activated T cells, SMAD, and c-fos (reviewed in reference 73). GATA-4 activity is also directly modulated by signaling cascades; ERK and p38 MAPK phosphorylate and enhance GATA-4 transcriptional activation domains (15,41), while glycogen synthase kinase (GSK3␤) phosphorylates the GATA-4 DNA binding domain and inhibits nuclear GATA-4 accumu- lation (50). Through its cooperative interaction with other transcriptional regulators, GATA-4 serves as a nuclear integrator of several signaling pathways, most notably calcineurin, MAPK, PI3 kinase, and receptor serine-threonine kinases.…”
Section: Discussionmentioning
confidence: 99%